Carbon nanofiber composite material and preparation method thereof
By blending modified filler and polyimide with modified carbon nanofibers, carbon nanofiber composite materials with good electromagnetic shielding effect are prepared, and the problem of general electromagnetic shielding effect of carbon nanofiber composite materials in the prior art is solved.
Patent Information
- Application Number
- CN202411871197.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-03-14
AI Technical Summary
At this stage, the electromagnetic shielding effect of carbon nanofiber composite materials is average and cannot effectively reduce electromagnetic interference.
After mixing the modified filler, polyacrylonitrile and N,N-dimethylformamide, it is electrospinned and carbonized under high temperature conditions to produce modified carbon nanofibers. Then, substances such as 4,4'-oxybisphthalic anhydride are reacted to form polyimide, blended with modified carbon nanofibers, sodium persulfate and aniline are added to form polyaniline molecular chains, and carbon nanofiber composite materials are prepared.
The carbon nanofiber composite material prepared by this method has a good electromagnetic shielding effect, and can effectively attenuate electromagnetic waves through multiple scattering and metal doping to achieve the purpose of shielding electromagnetic interference.
Smart Images

Figure BDA0005195805960000111
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of carbon nanofiber composite material preparation, and in particular to a carbon nanofiber composite material and a preparation method thereof. Background Art
[0002] With the development of advanced wireless communication technology and the electronics industry, especially in the fields of military, aviation, aerospace, machinery, energy, etc., higher requirements are put forward for the densification, integration and lightweight of chips. However, with the high integration of chips, heat accumulates in large quantities in components, which has a huge impact on the stability, reliability and life of the equipment. These electronic devices will inevitably generate a large amount of electromagnetic wave radiation when in use. Electromagnetic radiation is considered to be the fourth largest type of pollution after water pollution, noise pollution and air pollution. The electromagnetic interference caused by electromagnetic radiation will not only affect the normal operation of communication facilities, hospital instruments, and aerospace equipment, but also endanger the normal life of human beings, bringing severe challenges to people's physical health. In order to reduce the harm caused by electromagnetics, high-performance electromagnetic shielding materials that can reduce electromagnetic interference are urgently needed. Summary of the invention
[0003] The purpose of the present invention is to provide a carbon nanofiber composite material and a preparation method thereof, which solves the problem that the electromagnetic shielding effect of the carbon nanofiber composite material at present is mediocre.
[0004] The purpose of the present invention can be achieved through the following technical solutions:
[0005] A method for preparing a carbon nanofiber composite material comprises the following steps:
[0006] Step A1: after the modified filler, polyacrylonitrile and N, N-dimethylformamide are uniformly mixed, electrospinning is performed to obtain modified fibers, and the modified fibers are placed in a tubular furnace, heated to 200-300°C at a heating rate of 1.5-2°C / min, and kept warm for 2-3 hours, and then heated to 800-850°C at a heating rate of 5°C in a nitrogen atmosphere, and kept warm for 2-3 hours to obtain modified carbon nanofibers;
[0007] Step A2: 4,4'-oxydiphthalic anhydride, hexafluorodianhydride, diaminodiphenyl ether, 3,5-diaminobenzoic acid and dimethylacetamide are mixed, nitrogen is introduced for protection, and the mixture is reacted for 20-25 hours at a speed of 300-500 r / min and a temperature of 30-40° C., triethylamine and acetic anhydride are added, and the reaction is continued for 20-25 hours, methanol is added, the filtrate is removed by filtration, and the filter cake is kept warm for 10-15 hours at a temperature of 210-220° C. to obtain a pretreated polyimide;
[0008] Step A3: The pretreated polyimide, aniline, dicyclohexylcarbodiimide and N,N-dimethylformamide are mixed evenly, and reacted for 3-5 hours at a speed of 120-150r / min and a temperature of 25-30°C to obtain a modified polyimide. The modified polyimide, modified carbon nanofiber and N,N-dimethylformamide are mixed evenly, and stirred at a speed of 60-80r / min, a temperature of 10-15°C, and a pH value of 1-2, and ammonium persulfate and aniline are added to react for 20-25 hours, and then dried to obtain a carbon nanofiber composite material.
[0009] Furthermore, the usage ratio of the modified filler, polyacrylonitrile and N,N-dimethylformamide described in step A1 is 1 g:2 g:20 mL.
[0010] Furthermore, the molar ratio of 4,4'-oxydiphthalic anhydride, hexafluorodianhydride, diaminodiphenyl ether, 3,5-diaminobenzoic acid, triethylamine and acetic anhydride in step A2 is 2:1:2.5:0.5:4:1.
[0011] Furthermore, in the preparation process of the modified polyimide described in step A3, the molar ratio of carboxyl, aniline and dicyclohexylcarbodiimide on the pretreated polyimide is 1:1:1.1, the mass ratio of modified polyimide, modified carbon nanofiber and aniline is 10:1:2, and the amount of potassium persulfate used is 5‰ of the mass of aniline.
[0012] Further, the modified filler is prepared by the following steps:
[0013] Step B1: dispersing carbon nanotubes in ethanol, stirring and adding KH560 and deionized water at a speed of 120-150 r / min and a temperature of 60-70°C, reacting for 1-1.5 hours to obtain pretreated carbon nanotubes, and uniformly mixing the pretreated carbon nanotubes, 2-aminoimidazole and toluene, reacting for 3-5 hours at a speed of 150-200 r / min, a temperature of 20-25°C and a pH value of 10-11 to obtain modified carbon nanotubes.
[0014] Step B2: uniformly mix the modified carbon nanotubes, 2-methylimidazole and methanol, perform ultrasonic treatment and add cobalt nitrate hexahydrate and nickel nitrate hexahydrate at a frequency of 20-30kHz and a temperature of 35-40°C, react for 3-5 hours, filter and remove the filtrate, disperse the substrate in toluene, introduce nitrogen protection, stir and add isocyanatepropyltriethoxysilane and dibutyltin dilaurate at a speed of 120-150r / min and a temperature of 20-30°C, react for 1-1.5 hours to obtain a precursor;
[0015] Step B3: dissolving cellulose in N-methylmorpholine-N-oxide, introducing nitrogen protection, stirring and adding isocyanatepropyltriethoxysilane and dibutyltin dilaurate at a speed of 150-200 r / min and a temperature of 20-30°C, and reacting for 1-1.5 hours to obtain modified cellulose; uniformly mixing the modified cellulose, precursor, tetrabutyl titanate and ethanol, stirring and adding deionized water and hydrochloric acid at a speed of 300-500 r / min and a temperature of 65-70°C, and reacting for 2-3 hours to obtain a modified filler.
[0016] Furthermore, the amount of KH560 used in step B1 is 3% of the mass of the carbon nanotubes, and the molar ratio of the epoxy groups on the pretreated carbon nanotubes to the amino groups on the 2-aminoimidazole is 1:1.
[0017] Furthermore, the amount ratio of the modified carbon nanotubes, 2-methylimidazole, methanol, cobalt nitrate hexahydrate and nickel nitrate hexahydrate described in step B2 is 1g:1g:50mL:1.25g:1.25g, the amount of isocyanatepropyltriethoxysilane is 3% of the mass of the substrate, and the amount of dibutyltin dilaurate is 1% of the mass of isocyanatetriethoxysilane.
[0018] Furthermore, the amount ratio of cellulose and isocyanatepropyltriethoxysilane described in step B3 is 1g:2mL, the amount of dibutyltin dilaurate is 1% of the mass of isocyanatetriethoxysilane, and the amount ratio of modified cellulose, precursor, tetrabutyl titanate, ethanol, deionized water and hydrochloric acid is 3g:1g:3mL:50mL:3mL:1mL.
[0019] Beneficial effects of the present invention: A carbon nanofiber composite material disclosed by the present invention is prepared by uniformly mixing modified filler, polyacrylonitrile and N,N-dimethylformamide as raw materials, electrostatic spinning, and carbonizing at high temperature to obtain modified carbon nanofibers, reacting 4,4'-oxydiphthalic anhydride, hexafluorodianhydride, diaminodiphenyl ether and 3,5-diaminobenzoic acid to form polyimide acid, and then heat preservation at high temperature to obtain pretreated polyimide, reacting the pretreated polyimide with aniline to make the carboxyl group on the pretreated polyimide and the amino group on the aniline dehydrate to obtain modified polyimide, dissolving the modified polyimide in N,N-dimethylformamide and uniformly blending with the modified carbon nanofibers, adding sodium persulfate and aniline to form polyaniline molecular chains on the side chains of the polyimide molecules to obtain the carbon nanofiber composite material.
[0020] The modified filler is treated with KH560 using carbon nanotubes as raw materials, so that epoxy groups are grafted on the surface of the carbon nanotubes to obtain pretreated carbon nanotubes, the pretreated carbon nanotubes are reacted with 2-aminoimidazole, so that the epoxy groups on the pretreated carbon nanotubes react with the amino groups on the 2-aminoimidazole to form hydroxyl groups to obtain modified carbon nanotubes, the modified carbon nanotubes and 2-methylimidazole are uniformly mixed, cobalt nitrate hexahydrate and nickel nitrate hexahydrate are added, imidazole cobalt and imidazole nickel are coated on the surface of the modified carbon nanotubes, and then added Propyl triethoxysilane is used to react the isocyanate group on the isocyanate triethoxysilane with the hydroxyl group to obtain a precursor; cellulose is reacted with isocyanate triethoxysilane, the hydroxyl group on the cellulose reacts with the isocyanate group of isocyanate triethoxysilane to obtain modified cellulose; the modified cellulose, the precursor and tetrabutyl titanate are reacted under the action of deionized water, the siloxane on the modified cellulose and the precursor is hydrolyzed into silanol groups, which are hydrolyzed and condensed with tetrabutyl titanate to obtain a modified filler.
[0021] During the high-temperature carbonization process of the modified fiber, a carbonized material with a smooth surface, multiple apertures, and a complex multi-channel grid can be formed, which causes multiple scattering of electromagnetic waves in the process of passing through the material, thereby attenuating the electromagnetic waves. At the same time, the interior contains nickel, cobalt and titanium metal doping. When the electromagnetic wave encounters the metal, it will also be reflected on the metal surface due to the impedance mismatch between different metals and the air. The metal can absorb the electromagnetic wave and excite the movement of electrons on the inner wall of the metal, thereby converting the electromagnetic wave into heat energy. The composite material molecules contain polyaniline segments, which can contact the modified carbon nanofibers to form a conductive path. When the electromagnetic wave contacts the material, the electric field component of the electromagnetic wave will cause the electrons of the composite material to accelerate, thereby generating an electromagnetic field opposite to the incident wave, thereby offsetting the electromagnetic wave and achieving the effect of shielding the electromagnetic wave. DETAILED DESCRIPTION
[0022] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0023] Embodiment 1: A method for preparing a carbon nanofiber composite material, comprising the following steps:
[0024] Step A1: after the modified filler, polyacrylonitrile and N,N-dimethylformamide are uniformly mixed, electrospinning is performed to obtain modified fibers, and the modified fibers are placed in a tubular furnace, heated to 200°C at a heating rate of 1.5°C / min, and kept warm for 2 hours, and then heated to 800°C at a nitrogen atmosphere at a heating rate of 5°C, and kept warm for 2 hours to obtain modified carbon nanofibers;
[0025] Step A2: 4,4'-oxydiphthalic anhydride, hexafluorodianhydride, diaminodiphenyl ether, 3,5-diaminobenzoic acid and dimethylacetamide are mixed, nitrogen is introduced for protection, and the reaction is carried out for 20 hours at a speed of 300 r / min and a temperature of 30° C., and then triethylamine and acetic anhydride are added, and the reaction is continued for 20 hours, and methanol is added, and the filtrate is removed by filtration, and the filter cake is kept at a temperature of 210° C. for 10 hours to obtain a pretreated polyimide;
[0026] Step A3: The pretreated polyimide, aniline, dicyclohexylcarbodiimide and N,N-dimethylformamide are mixed evenly, and reacted at a speed of 120 r / min and a temperature of 25°C for 3 hours to obtain a modified polyimide; the modified polyimide, modified carbon nanofiber and N,N-dimethylformamide are mixed evenly, and stirred at a speed of 60 r / min, a temperature of 10°C and a pH value of 1, and ammonium persulfate and aniline are added to react for 20 hours, and then dried to obtain a carbon nanofiber composite material.
[0027] The modified filler, polyacrylonitrile and N,N-dimethylformamide described in step A1 are used in a ratio of 1 g:2 g:20 mL.
[0028] The molar ratio of 4,4'-oxydiphthalic anhydride, hexafluorodianhydride, diaminodiphenyl ether, 3,5-diaminobenzoic acid, triethylamine and acetic anhydride in step A2 is 2:1:2.5:0.5:4:1.
[0029] In the preparation process of the modified polyimide described in step A3, the molar ratio of carboxyl, aniline and dicyclohexylcarbodiimide on the pretreated polyimide is 1:1:1.1, the mass ratio of modified polyimide, modified carbon nanofiber and aniline is 10:1:2, and the amount of potassium persulfate used is 5‰ of the mass of aniline.
[0030] The modified filler is prepared by the following steps:
[0031] Step B1: dispersing carbon nanotubes in ethanol, stirring and adding KH560 and deionized water at a speed of 120 r / min and a temperature of 60° C., and reacting for 1 h to obtain pretreated carbon nanotubes; mixing the pretreated carbon nanotubes, 2-aminoimidazole and toluene uniformly, and reacting for 3 h at a speed of 150 r / min, a temperature of 20° C. and a pH value of 10 to obtain modified carbon nanotubes;
[0032] Step B2: The modified carbon nanotubes, 2-methylimidazole and methanol were mixed uniformly, and cobalt nitrate hexahydrate and nickel nitrate hexahydrate were added under ultrasonic treatment at a frequency of 20 kHz and a temperature of 35°C. After reacting for 3 hours, the filtrate was removed by filtration, and the substrate was dispersed in toluene, and nitrogen was introduced for protection. At a speed of 120 r / min and a temperature of 20°C, propyltriethoxysilane and dibutyltin dilaurate were added under stirring, and the reaction was carried out for 1 hour to obtain a precursor;
[0033] Step B3: Dissolve cellulose in N-methylmorpholine-N-oxide, introduce nitrogen protection, stir and add isocyanatepropyltriethoxysilane and dibutyltin dilaurate at a speed of 150 r / min and a temperature of 20°C, and react for 1 hour to obtain modified cellulose. Mix the modified cellulose, precursor, tetrabutyl titanate and ethanol evenly, stir and add deionized water and hydrochloric acid at a speed of 300 r / min and a temperature of 65°C, and react for 2 hours to obtain a modified filler.
[0034] The amount of KH560 used in step B1 is 3% of the mass of the carbon nanotubes, and the molar ratio of the epoxy groups on the pretreated carbon nanotubes to the amino groups on the 2-aminoimidazole is 1:1.
[0035] The amount ratio of the modified carbon nanotubes, 2-methylimidazole, methanol, cobalt nitrate hexahydrate and nickel nitrate hexahydrate described in step B2 is 1g:1g:50mL:1.25g:1.25g, the amount of propyltriethoxysilane is 3% of the mass of the substrate, and the amount of dibutyltin dilaurate is 1% of the mass of triethoxysilane isocyanate.
[0036] The amount ratio of cellulose and isocyanatepropyltriethoxysilane described in step B3 is 1g:2mL, the amount of dibutyltin dilaurate is 1% of the mass of isocyanatetriethoxysilane, and the amount ratio of modified cellulose, precursor, tetrabutyl titanate, ethanol, deionized water and hydrochloric acid is 3g:1g:3mL:50mL:3mL:1mL.
[0037] Embodiment 2: A method for preparing a carbon nanofiber composite material, comprising the following steps:
[0038] Step A1: after the modified filler, polyacrylonitrile and N,N-dimethylformamide are uniformly mixed, electrospinning is performed to obtain modified fibers, and the modified fibers are placed in a tubular furnace, heated to 300°C at a heating rate of 1.5°C / min, and kept warm for 2 hours, and then heated to 800°C at a nitrogen atmosphere at a heating rate of 5°C, and kept warm for 3 hours to obtain modified carbon nanofibers;
[0039] Step A2: 4,4'-oxydiphthalic anhydride, hexafluorodianhydride, diaminodiphenyl ether, 3,5-diaminobenzoic acid and dimethylacetamide are mixed, nitrogen is introduced for protection, and the reaction is carried out for 25 hours at a speed of 300 r / min and a temperature of 35°C. Triethylamine and acetic anhydride are added, and the reaction is continued for 20 hours. Methanol is added, and the filtrate is removed by filtration. The filter cake is kept at a temperature of 215°C for 15 hours to obtain a pretreated polyimide;
[0040] Step A3: The pretreated polyimide, aniline, dicyclohexylcarbodiimide and N,N-dimethylformamide are mixed evenly, and reacted at a speed of 120 r / min and a temperature of 30°C for 4 hours to obtain a modified polyimide; the modified polyimide, modified carbon nanofiber and N,N-dimethylformamide are mixed evenly, and stirred at a speed of 60 r / min, a temperature of 15°C and a pH value of 1, and ammonium persulfate and aniline are added to react for 25 hours, and then dried to obtain a carbon nanofiber composite material.
[0041] The modified filler, polyacrylonitrile and N,N-dimethylformamide described in step A1 are used in a ratio of 1 g:2 g:20 mL.
[0042] The molar ratio of 4,4'-oxydiphthalic anhydride, hexafluorodianhydride, diaminodiphenyl ether, 3,5-diaminobenzoic acid, triethylamine and acetic anhydride in step A2 is 2:1:2.5:0.5:4:1.
[0043] In the preparation process of the modified polyimide described in step A3, the molar ratio of carboxyl, aniline and dicyclohexylcarbodiimide on the pretreated polyimide is 1:1:1.1, the mass ratio of modified polyimide, modified carbon nanofiber and aniline is 10:1:2, and the amount of potassium persulfate used is 5‰ of the mass of aniline.
[0044] The modified filler is prepared by the following steps:
[0045] Step B1: dispersing carbon nanotubes in ethanol, stirring and adding KH560 and deionized water at a speed of 120 r / min and a temperature of 65° C., reacting for 1.5 h to obtain pretreated carbon nanotubes, and mixing the pretreated carbon nanotubes, 2-aminoimidazole and toluene uniformly, reacting for 4 h at a speed of 150 r / min, a temperature of 25° C. and a pH value of 10 to obtain modified carbon nanotubes.
[0046] Step B2: The modified carbon nanotubes, 2-methylimidazole and methanol were mixed evenly, and cobalt nitrate hexahydrate and nickel nitrate hexahydrate were added under ultrasonic treatment at a frequency of 25 kHz and a temperature of 40°C. After reacting for 4 hours, the filtrate was removed by filtration, and the substrate was dispersed in toluene, and nitrogen was introduced for protection. At a speed of 120 r / min and a temperature of 25°C, propyltriethoxysilane and dibutyltin dilaurate were added under stirring, and the reaction was carried out for 1.5 hours to obtain a precursor;
[0047] Step B3: Dissolve cellulose in N-methylmorpholine-N-oxide, introduce nitrogen protection, stir and add isocyanatepropyltriethoxysilane and dibutyltin dilaurate at a speed of 150 r / min and a temperature of 25°C, and react for 1.5 hours to obtain modified cellulose. Mix the modified cellulose, precursor, tetrabutyl titanate and ethanol evenly, stir and add deionized water and hydrochloric acid at a speed of 300 r / min and a temperature of 70°C, and react for 2 hours to obtain a modified filler.
[0048] The amount of KH560 used in step B1 is 3% of the mass of the carbon nanotubes, and the molar ratio of the epoxy groups on the pretreated carbon nanotubes to the amino groups on the 2-aminoimidazole is 1:1.
[0049] The amount ratio of the modified carbon nanotubes, 2-methylimidazole, methanol, cobalt nitrate hexahydrate and nickel nitrate hexahydrate described in step B2 is 1g:1g:50mL:1.25g:1.25g, the amount of propyltriethoxysilane is 3% of the mass of the substrate, and the amount of dibutyltin dilaurate is 1% of the mass of triethoxysilane isocyanate.
[0050] The amount ratio of cellulose and isocyanatepropyltriethoxysilane described in step B3 is 1g:2mL, the amount of dibutyltin dilaurate is 1% of the mass of isocyanatetriethoxysilane, and the amount ratio of modified cellulose, precursor, tetrabutyl titanate, ethanol, deionized water and hydrochloric acid is 3g:1g:3mL:50mL:3mL:1mL.
[0051] Embodiment 3: A method for preparing a carbon nanofiber composite material, comprising the following steps:
[0052] Step A1: after the modified filler, polyacrylonitrile and N, N-dimethylformamide are uniformly mixed, electrospinning is performed to obtain modified fibers, and the modified fibers are placed in a tubular furnace, heated to 300°C at a heating rate of 2°C / min, and kept warm for 3 hours, and then heated to 850°C at a heating rate of 5°C in a nitrogen atmosphere, and kept warm for 3 hours to obtain modified carbon nanofibers;
[0053] Step A2: 4,4'-oxydiphthalic anhydride, hexafluorodianhydride, diaminodiphenyl ether, 3,5-diaminobenzoic acid and dimethylacetamide are mixed, nitrogen is introduced for protection, and the reaction is carried out for 25 hours at a speed of 500 r / min and a temperature of 40°C. Triethylamine and acetic anhydride are added, and the reaction is continued for 25 hours. Methanol is added, and the filtrate is removed by filtration. The filter cake is kept at a temperature of 220°C for 15 hours to obtain a pretreated polyimide;
[0054] Step A3: The pretreated polyimide, aniline, dicyclohexylcarbodiimide and N,N-dimethylformamide are mixed evenly, and reacted at a speed of 150 r / min and a temperature of 30°C for 5 hours to obtain a modified polyimide; the modified polyimide, modified carbon nanofiber and N,N-dimethylformamide are mixed evenly, and stirred at a speed of 80 r / min, a temperature of 15°C and a pH value of 2, and ammonium persulfate and aniline are added to react for 25 hours, and then dried to obtain a carbon nanofiber composite material.
[0055] The modified filler, polyacrylonitrile and N,N-dimethylformamide described in step A1 are used in a ratio of 1 g:2 g:20 mL.
[0056] The molar ratio of 4,4'-oxydiphthalic anhydride, hexafluorodianhydride, diaminodiphenyl ether, 3,5-diaminobenzoic acid, triethylamine and acetic anhydride in step A2 is 2:1:2.5:0.5:4:1.
[0057] In the preparation process of the modified polyimide described in step A3, the molar ratio of carboxyl, aniline and dicyclohexylcarbodiimide on the pretreated polyimide is 1:1:1.1, the mass ratio of modified polyimide, modified carbon nanofiber and aniline is 10:1:2, and the amount of potassium persulfate used is 5‰ of the mass of aniline.
[0058] The modified filler is prepared by the following steps:
[0059] Step B1: dispersing carbon nanotubes in ethanol, stirring and adding KH560 and deionized water at a speed of 150 r / min and a temperature of 70°C, and reacting for 1.5 hours to obtain pretreated carbon nanotubes, and mixing the pretreated carbon nanotubes, 2-aminoimidazole and toluene uniformly, and reacting for 5 hours at a speed of 200 r / min, a temperature of 25°C and a pH value of 11 to obtain modified carbon nanotubes.
[0060] Step B2: The modified carbon nanotubes, 2-methylimidazole and methanol were mixed uniformly, and cobalt nitrate hexahydrate and nickel nitrate hexahydrate were added under ultrasonic treatment at a frequency of 30 kHz and a temperature of 40°C. After reacting for 5 hours, the filtrate was removed by filtration, and the substrate was dispersed in toluene, and nitrogen was introduced for protection. At a speed of 150 r / min and a temperature of 30°C, propyltriethoxysilane and dibutyltin dilaurate were added under stirring, and the reaction was carried out for 1.5 hours to obtain a precursor;
[0061] Step B3: Dissolve cellulose in N-methylmorpholine-N-oxide, introduce nitrogen protection, stir and add isocyanatepropyltriethoxysilane and dibutyltin dilaurate at a speed of 200 r / min and a temperature of 30°C, and react for 1.5 hours to obtain modified cellulose. Mix the modified cellulose, precursor, tetrabutyl titanate and ethanol evenly, stir and add deionized water and hydrochloric acid at a speed of 500 r / min and a temperature of 70°C, and react for 3 hours to obtain a modified filler.
[0062] The amount of KH560 used in step B1 is 3% of the mass of the carbon nanotubes, and the molar ratio of the epoxy groups on the pretreated carbon nanotubes to the amino groups on the 2-aminoimidazole is 1:1.
[0063] The amount ratio of the modified carbon nanotubes, 2-methylimidazole, methanol, cobalt nitrate hexahydrate and nickel nitrate hexahydrate described in step B2 is 1g:1g:50mL:1.25g:1.25g, the amount of propyltriethoxysilane is 3% of the mass of the substrate, and the amount of dibutyltin dilaurate is 1% of the mass of triethoxysilane isocyanate.
[0064] The amount ratio of cellulose and isocyanatepropyltriethoxysilane described in step B3 is 1g:2mL, the amount of dibutyltin dilaurate is 1% of the mass of isocyanatetriethoxysilane, and the amount ratio of modified cellulose, precursor, tetrabutyl titanate, ethanol, deionized water and hydrochloric acid is 3g:1g:3mL:50mL:3mL:1mL.
[0065] Comparative Example 1. Compared with Example 1, this comparative example is a mixture of 4,4'-oxydiphthalic anhydride, hexafluorodianhydride, diaminodiphenyl ether and dimethylacetamide, and nitrogen protection is introduced. At a speed of 300 r / min and a temperature of 30°C, the mixture is reacted for 20 hours. Then, triethylamine and acetic anhydride are added, and the reaction is continued for 20 hours. Methanol is added, and the filtrate is removed by filtration. The filter cake is kept warm at a temperature of 210°C for 10 hours. The obtained product replaces the modified polyimide, and the remaining steps are the same.
[0066] Comparative Example 2: Compared with Example 1, this comparative example uses amino carbon nanotubes dispersed in toluene, and nitrogen protection is introduced. At a rotation speed of 120 r / min and a temperature of 20°C, stirring is performed and triethoxypropyl isocyanate and dibutyltin dilaurate are added. The reaction is carried out for 1 hour. The obtained product replaces the modified precursor, and the remaining steps are the same.
[0067] Comparative Example 3: Compared with Example 1, no modified cellulose was added in this comparative example, and the remaining steps were the same.
[0068] Comparative Example 4: Compared with Example 1, tetrabutyl titanate was not added in this comparative example, and the remaining steps were the same.
[0069] The composite materials prepared in Examples 1-3 and Comparative Examples 1-4 were made into specimens with a thickness of 20 μm and tested in accordance with ASTM D4935 standard with a scanning frequency of 30 MHz-3 GHz and test conditions of high temperature and high humidity (85°C*85% relative humidity). The shielding energy efficiency was tested and the test results are shown in Table 1 below.
[0070] Table 1
[0071]
[0072] It can be seen from Table 1 above that the present application has a very good electromagnetic shielding effect.
[0073] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.
Claims
1. A method for preparing a carbon nanofiber composite material, characterized in that: The specific steps include: Step A1: after uniformly mixing the modified filler, polyacrylonitrile and N,N-dimethylformamide, electrospinning is performed to obtain modified fibers, and the modified fibers are placed in a tubular furnace and kept at high temperature to obtain modified carbon nanofibers; Step A2: 4,4'-oxydiphthalic anhydride, hexafluorodianhydride, diaminodiphenyl ether, 3,5-diaminobenzoic acid and dimethylacetamide are mixed, nitrogen is introduced for protection, triethylamine and acetic anhydride are added after the reaction, the reaction is continued, methanol is added, the filtrate is removed by filtration, and the filter cake is kept at high temperature to obtain a pretreated polyimide; Step A3: pretreated polyimide, aniline, dicyclohexylcarbodiimide and N,N-dimethylformamide are mixed and reacted to obtain modified polyimide, modified polyimide, modified carbon nanofiber and N,N-dimethylformamide are mixed and stirred, and ammonium persulfate and aniline are added, and after reaction, drying is performed to obtain a carbon nanofiber composite material.
2. The method for preparing a carbon nanofiber composite material according to claim 1, characterized in that: The modified filler, polyacrylonitrile and N,N-dimethylformamide described in step A1 are used in a ratio of 1 g:2 g:20 mL.
3. The method for preparing a carbon nanofiber composite material according to claim 1, characterized in that: The molar ratio of 4,4'-oxydiphthalic anhydride, hexafluorodianhydride, diaminodiphenyl ether, 3,5-diaminobenzoic acid, triethylamine and acetic anhydride in step A2 is 2:1:2.5:0.5:4:
1.
4. The method for preparing a carbon nanofiber composite material according to claim 1, characterized in that: In the preparation process of the modified polyimide described in step A3, the molar ratio of carboxyl, aniline and dicyclohexylcarbodiimide on the pretreated polyimide is 1:1:1.1, and the mass ratio of the modified polyimide, the modified carbon nanofiber and aniline is 10:1:
2.
5. The method for preparing a carbon nanofiber composite material according to claim 1, characterized in that: The modified filler is prepared by the following steps: Step B1: dispersing carbon nanotubes in ethanol, stirring and adding KH560 and deionized water to react to obtain pretreated carbon nanotubes, mixing the pretreated carbon nanotubes, 2-aminoimidazole and toluene to react to obtain modified carbon nanotubes, Step B2: The modified carbon nanotubes, 2-methylimidazole and methanol are mixed and ultrasonically treated, and cobalt nitrate hexahydrate and nickel nitrate hexahydrate are added to react, and the filtrate is filtered to remove the filtrate, and the substrate is dispersed in toluene, nitrogen is introduced for protection, and isocyanatepropyltriethoxysilane and dibutyltin dilaurate are added to react with stirring to obtain a precursor; Step B3: dissolving cellulose in N-methylmorpholine-N-oxide, introducing nitrogen protection, stirring and adding isocyanatepropyltriethoxysilane and dibutyltin dilaurate to react to obtain modified cellulose; mixing the modified cellulose, precursor, tetrabutyl titanate and ethanol, stirring and adding deionized water and hydrochloric acid to react to obtain a modified filler.
6. The method for preparing a carbon nanofiber composite material according to claim 5, characterized in that: The amount of KH560 used in step B1 is 3% of the mass of the carbon nanotubes, and the molar ratio of the epoxy groups on the pretreated carbon nanotubes to the amino groups on the 2-aminoimidazole is 1:
1.
7. The method for preparing a carbon nanofiber composite material according to claim 5, characterized in that: The modified carbon nanotubes, 2-methylimidazole, methanol, cobalt nitrate hexahydrate and nickel nitrate hexahydrate described in step B2 are used in a ratio of 1 g: 1 g: 50 mL: 1.25 g: 1.25 g, and the amount of triethoxypropylsilane isocyanate is 3% of the substrate weight.
8. The method for preparing a carbon nanofiber composite material according to claim 5, characterized in that: The amount ratio of cellulose and isocyanatepropyltriethoxysilane described in step B3 is 1g:2mL, and the amount ratio of modified cellulose, precursor, tetrabutyl titanate, ethanol, deionized water and hydrochloric acid is 3g:1g:3mL:50mL:3mL:1mL.
9. A carbon nanofiber composite material, characterized in that: Prepared according to any one of claims 1 to 8.